Pengembangan Instrumen Penilaian Afektif Berbasis Problem Based Learning Sebagai Upaya Preventif Darurat Narkoba Pada Siswa SMA Negeri 15 Semarang (Universitas Negeri Semarang, 2023)
Education plays a very important role in building the character of teenagers to be more aware of the dangers of drugs. Moreover, the implementation of the 2013 curriculum emphasizes building a strong character for each student. This is based on the many occurrences of deterioration of the nation's character which can be seen from the many acts of corruption, violence, drug abuse and other actions. This is what underlies this research as an emergency drug prevention effort in adolescents, especially high school students. The development of assessment instruments using R & D according to Sugiyono. The attitude assessment instrument developed is used as a solution and can be used as an alternative for teachers in conducting the process of assessing adolescent attitudes towards drug emergencies in accordance with the 2013 Curriculum. The object of research data sources are students of class XI.IPS.1 and class XI.IPA.2 SMAN 15 Semarang , the data were obtained through the validity and reliability of the attitude assessment observation sheet, the process of developing an instrument for assessing honesty, discipline, responsibility and caring for drug emergencies each consisting of 4 indicators, the assessment instrument was valid according to 2 (two) validators in the curriculum and field of study. learning evaluation. The assessment instrument is said to be effective/successful, because the results of the instrument reliability analysis produce an r table value of 0.9997 for all subjects, this number exceeds the r coefficient value of the benchmark value of (0.6). This assessment instrument is good to use to provide students with objective views and attitudes in highlighting the dangers of drugs to stay away from their abuse.